Pengaruh Profitabilitas, Reputasi Auditor, Audit Tenure dan Ukuran Perusahaan terhadap Audit Delay pada Perusahaan Manufaktur Subsektor Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia periode 2022-2024 - Ineke Aprilya Nasution; Paskah Ria Sitorus; Lamtiur Lidia Gultom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The relationship between audit delays and firm size, auditor reputation, audit time, and profitability is investigated in this study. Companies in the food and beverage sector that are scheduled to list on the Indonesia Stock Exchange between 2022 and 2024 are the main subject of this research. Audit delay refers to the length of time elapsed after the end of a company's fiscal year for the independent auditor to complete its work and submit its report. 58 of the 98 businesses listed on the Indonesia Stock Exchange provided 174 data points using a purposive sample technique. The data may be used to obtain useful computations and insights using multiple linear regression analysis techniques using SPSS. This study indicates that a number of reasons might cause audit delays. Tenure as an auditor is one. Profitability is another. Third, audit delays are unaffected by an auditor's reputation. Fourth, audit delays are negatively correlated with firm size. Lastly, there is a positive relationship between audit delays and profitability. Concurrent testing findings show that audit duration is influenced by auditor tenure, profitability, reputation, and firm size